2014
DOI: 10.1172/jci75660
|View full text |Cite
|
Sign up to set email alerts
|

Skin exposure promotes a Th2-dependent sensitization to peanut allergens

Abstract: Cells were seeded in 24-well plates and stimulated with CPE or soy extract. Cells were recovered at several time points for RNA isolation with the RNeasy Mini Kit (Qiagen).Bone marrow-derived DCs. Bone marrow cells were collected from femurs and cultured for 10 days in RPMI 1640 with l-glutamine (Gibco, Life Technologies), supplemented with 10% fetal bovine serum (Gemini Bio-products), penicillin/streptomycin (Gibco, Life Technologies), 50 μM 2-Mercaptoethanol (Sigma-Aldrich), and 20 ng/ml GM-CSF (Peprotech). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
208
0
4

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 193 publications
(225 citation statements)
references
References 67 publications
(87 reference statements)
6
208
0
4
Order By: Relevance
“…Our findings are in line with previous studies demonstrating that the matrix from allergen sources contains compounds that might aid allergic sensitization and lipids may play a fundamental role 1, 2, 3. The pro‐inflammatory mediators produced by KC upon PNL stimulation may perhaps lead to barrier disruption and promote the proper environment allowing Ara h 1 or Ara h 2 to penetrate the epidermis and recruit neighboring cells involved in the allergic sensitization process 6.…”
Section: Figuresupporting
confidence: 91%
See 3 more Smart Citations
“…Our findings are in line with previous studies demonstrating that the matrix from allergen sources contains compounds that might aid allergic sensitization and lipids may play a fundamental role 1, 2, 3. The pro‐inflammatory mediators produced by KC upon PNL stimulation may perhaps lead to barrier disruption and promote the proper environment allowing Ara h 1 or Ara h 2 to penetrate the epidermis and recruit neighboring cells involved in the allergic sensitization process 6.…”
Section: Figuresupporting
confidence: 91%
“…Exposure of infants to peanut oil‐containing lotions was described as a risk factor for the development of peanut allergy 1. There is evidence that only peanut extracts containing lipids were able to induce sensitization 2, 3. How this occurs at the molecular level is still unknown.…”
Section: Figurementioning
confidence: 99%
See 2 more Smart Citations
“…In previous studies, it was demonstrated that skin exposure to peanut and OVA allergen is an effective route for inducing sensitization (Hsieh et al 2003;Tordesillas et al 2014). Building on those studies, the present study also indicated that there was a sensitizing ability for pigeon pea allergens via the skin route.…”
Section: Discussionsupporting
confidence: 75%